2021
DOI: 10.1101/2021.08.25.21262556
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Environmental Exposure to Volatile Organic Compounds is Associated with Endothelial Injury

Abstract: Objective: Volatile organic compounds (VOCs) are airborne toxicants abundant in outdoor and indoor air. High levels of VOCs are also present at various Superfund and other hazardous waste sites; however, little is known about the cardiovascular effects of VOCs. We hypothesized that ambient exposure to VOCs exacerbate cardiovascular disease (CVD) risk by depleting circulating angiogenic cells (CACs). Approach and Results: In this cross-sectional study, we recruited 375 non-smokers with low-to-high CVD risk an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Other than blood pressure, VOC is associated with increased cardiovascular mortality, heart failure hospitalizations, and ischemic heart disease mortality [27,28], and the mechanism underlying these health risks is assumed to be through the endothelial damage. Moreover, VOCs can exert an effect on insulin resistance which is the main factor in the development of diabetes [27,[29][30][31][32]. Yang et al also reported that high urinary t,t-MA increased the risk of diabetes regardless of smoking status and sex [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than blood pressure, VOC is associated with increased cardiovascular mortality, heart failure hospitalizations, and ischemic heart disease mortality [27,28], and the mechanism underlying these health risks is assumed to be through the endothelial damage. Moreover, VOCs can exert an effect on insulin resistance which is the main factor in the development of diabetes [27,[29][30][31][32]. Yang et al also reported that high urinary t,t-MA increased the risk of diabetes regardless of smoking status and sex [33].…”
Section: Discussionmentioning
confidence: 99%
“…Everson et al measured the BTEX and NO 2 exposure at the personal level and found out that those exposure and blood pressure have a positive association even in both short-term and long-term exposure as well as in lower concentrations [26]. Other than blood pressure, VOC is associated with increased cardiovascular mortality, heart failure hospitalizations, and ischemic heart disease mortality [27,28], and the mechanism underlying these health risks is assumed to be through the endothelial damage. Moreover, VOCs can exert an effect on insulin resistance which is the main factor in the development of diabetes [27,[29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%